FORMULASI SEDIAAN SALEP HIDROFILIK BERBAHAN BAKU DAUN KETEPENG CINA (Cassia alata L.) DENGAN PELARUT HEKSAN SEBAGAI ANTIFUNGI - Dwi wiwi (Jurnal Medika Hutama, 2022)
Ketepeng Cina (Cassia alata L.) the leaves can be used for the treatment of infections caused by bacteria such as syphilis, fungal infections such as ringworm, tinea versicolor, scabies. Ketepeng Cina leaves used leaves located in Bonto Lempangan Village, Bontoa District, Maros Regency. This study aims to determine how to make a hydrophilic ointment formulation based on Ketepeng Cina (Cassia alata L.) leaves with hexane as an antifungal solvent. Ketepeng Cina (Cassia alata L.) leaves were processed by extraction using the maceration method. The results of this study from several physical test results of test ointments with variations in concentrations of 1%,3%,5%, namely organoleptic tests obtained stable results, homogeneity obtained homogeneous results from concentrations of 1%3%,5%, pH test obtained appropriate results. with skin criteria, namely 4.5-6.5 from a concentration of 1%,3%,5%, the dispersion test did not show good dispersion results from a concentration of 1%,3%,5%, and the results of the inhibition test with a concentration of 1%,3 %,5% was able to inhibit the malasezzia furfur fungus with an inhibition zone of 5,6,7 mm in diameter and the positive control result (ketoconazole) was able to inhibit the malasezzia furfur fungus with an inhibition zone of 10 mm in diameter.